1999
DOI: 10.1038/sj.jea.7500028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a personal air sampler for twenty-four hour collection of fine particles and semivolatile organics1

Abstract: The U.S. EPA has conducted an evaluation of a commercially available lightweight fine particle personal sampler for use in human exposure and Ž . biomarker studies involving 24-h collections of particulate matter, particle-bound organics such as polycyclic aromatic hydrocarbons PAHs , and Ž . semivolatile organics PAHs . Independent laboratory evaluation of the prototype design, intended to produce a 2.5-mm aerodynamic diameter cut-point at Ž . Ž . a flow between 1.5 and 1.7 lpm liters per minute , indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…27 The sampler was connected to a pump operating at 1.7 l/min powered by batteries with inlet attached to the individual's breathing zone and was located by his bed during the night (total weight of the sampler 1 kg). 28…”
Section: Personal Exposure Monitoringmentioning
confidence: 99%
“…27 The sampler was connected to a pump operating at 1.7 l/min powered by batteries with inlet attached to the individual's breathing zone and was located by his bed during the night (total weight of the sampler 1 kg). 28…”
Section: Personal Exposure Monitoringmentioning
confidence: 99%
“…An intensive 5-year research effort to further this goal was conducted beginning in 1998 using guidance from the National Research Council (NRC, 1998). One major component of this effort involved longitudinal human exposure panel studies in an effort to better understand the contribution of particulate matter (PM) of ambient origin to total personal exposures over time (Williams et al, 1999;Evans et al, 2000;Williams et al, 2000a, b, c, d;Williams et al, 2002Williams et al, , 2003aWallace and Williams, 2005;Wallace et al, 2006a, b;McBride et al, 2007). Results from these studies showed that for fine PM mass and sulfate, a central monitoring site could serve as an adequate surrogate for exposure in community-based epidemiological studies (US EPA, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Latex allergen found on respirable rubber tire particles is likely common in urban air (125,126) and could lead to sensitization and respiratory symptoms. In addition, the physical action of motor vehicles on road dust, which is known to contain pollen grains, could lead to the production and resuspension of smaller respirable pollen fragments (37).…”
Section: Epidemiologic Evidence For Pollutant Mixtures Containing Pahmentioning
confidence: 99%